VD_FINDINFO Jug / 2024 / 256 vom 16. April 2024 - VD Tribunal cantonal (2024)
DIFFAMATION, MENACEDROIT PÉNAL, VIOLENCE CONTRE LES AUTORITÉS, REJET DE LA DEMANDE | 173 ch. 1 CP, 180 al. 1 CP, 285 ch. 1 CP